The effects of arsenic on oxidative stress responses in Xanthomonas campestris pv. phaseoli - Karnjana Hrimpeng; Skorn Mongkolsuk; Preeda Pakpian; Paiboon Vattanaviboon; Rojana Sukchawalit; Buttner, Mark; Chulabhorn Research Institute / Mahidol University / AIT Fellowship (CRI - MU- AIT) (Pathum Thani, Thailand : Asian Institute of Technology, 2007)
Being used as an insecticide and herbicide, arsenic is one of the first priority environmental pollutants contaminated in many agricultural soils. The oxidative stress responses of Xanthomonas campestris pv. phaseoli (Xp), a soil borne phytopathogenic bacteria, against the arsenic exposure were investigated. Pretreatment of Xp with sub-lethal concentrations of sodium arsenite [NaAsO2, As(III)] could induced cross protection against subsequent exposure to lethal doses of hydrogen peroxide (H202) and cumene hydroperoxide (CuOOH) but could not induced the protection against subsequence exposure to menadione (a superoxide generator). This implied that challenging the Xp with low concentrations of As(III) could trigger the defense mechanisms against peroxide rather than superoxide toxicity. The components and genes involved in As(III)-induced cross protection against oxidants killing were investigated. The results demonstrated that these protections were likely due to elevated scavenging enzyme levels including monofunctional catalase (KatA), alkyl hydroperoxide reductase (AhpC), and organic hydroperoxide resistance protein (Ohr). In addition, it was found that katA and ahpC genes play a role in As(III)-induced cross protection from H2O2 killing whereas the ohr and ahpC genes involved in As(III)-induced cross protection from CuOOH killing. Moreover, a mechanism responsible for As(III) toxicity in Xp was determined and found that the metalloid toxicity involved the increased production and accumulation of reactive oxygen species (ROS) including H20 2 and organic hydroperoxide. Finally, the effects of ROS scavenging enzymes on metals exposure were investigated. The result from As(III) sensitivity test against wild type Xp and various mutants, including Xp oxyR, Xp katA, Xp ahpC, Xp katA ahpC, Xp ohr, Xp ohr ahpC, and Xp gor, demonstrated that the peroxide detoxification enzymes are likely to play a physiological role on protecting Xp from As(III) toxicity. It is possible that generation of ROS ability of As(III) is one of the mechanisms responsible for As(III) toxicity. The effect of the ROS scavenging enzymes, catalase and AhpC, on mercury exposure were also investigated in wild type Xp and mutants including Xp HR (constitutively expression of catalase and AhpC), Xp oxyR, Xp katA, and Xp katA ahpC. By contrast, it was found that the mutants whose posses lower levels of catalase or AhpC were more resistant to mercury compared to those of wild type. This result indicated that Xp catalase and AhpC are likely to increase sensitivity of Xp to mercury toxicity. It is possible that these enzymes are involved in mercury cycling by converting less toxic form of mercury (Hg0) into more toxic form (Hg2+) as observed in Escherichia coli. The data elucidate that accumulated As(III) in the environment could alter the responses against oxidative stress in soil phytopathogenic bacteria. As a consequence, this alteration may affect plant-microbe interaction leading to change in bacterial pathogenesis.
A dissertation submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Environmental Engineering and Management Inter-University Program on Environmental Toxicology, Technology and Management
Thesis (Ph.D.) - Asian Institute of Technology - Chulabhorn Research Institute - Mahidol University, 2007
Keywords: Arsenic -- Toxicology; Arsenic -- Environmental aspects